Changes of Aboveground and Belowground Biomass Allocation in Four Dominant Grassland Species Across a Precipitation Gradient - Liu, Yongjie; Xu, Mingjie; Li, Guoe; Wang, Mingxia; Li, Zhenqing; De Boeck, Hans J. (Frontiers in Plant Science, 2021)
Climate change is predicted to affect plant growth, but also the allocation of biomass to aboveground and belowground plant parts. To date, studies have mostly focused on aboveground biomass, while belowground biomass and allocation patterns have received less attention. We investigated changes in biomass allocation along a controlled gradient of precipitation in an experiment with four plant species (Leymus chinensis, Stipa grandis, Artemisia frigida and Potentilla acaulis) dominant in Inner Mongolia steppe. Results show that aboveground biomass, belowground biomass and total biomass all increased with increasing growing season precipitation, as expected in this water-limited ecosystem. Biomass allocation patterns also changed along the precipitation gradient, but significant variation between species was apparent. Specifically, the belowground biomass: aboveground biomass ratio (i.e. B:A ratio) of S. grandis was not impacted by precipitation amount, while B:A ratios of the other three species changed in different ways along the gradient. Some of these differences in allocation strategies may be related to morphological differences, specifically, the presence of rhizomes or stolons, though no consistent patterns emerged. Isometric partitioning, i.e. constant allocation of biomass aboveground and belowground, seemed to occur for one species (S. grandis), but not for the three rhizome or stolon-forming ones. Indeed, for these species, the slope of the allometric regression between long-transformed belowground biomass and log-transformed aboveground biomass significantly differed from 1.0 and B:A ratios changed along the precipitation gradient. As changes in biomass allocation can affect ecosystem functioning and services, our results can be used as a basis for further studies into allocation patterns, especially in a context of environmental change.